Interrelationship between Income, Health and Environment : In a Case of Malaysia - Abdul Samad, Abdul Rahim (2005)

(untitled)
This paper examines the link between health indicators and the environmental variables withn a country widely dispersed on the economic development spectrum. While environment and income are seen to have an inverted-U shaped relationship (Environmental Kuznets Curve (EKC) hypothesis), it is also well established that environment and health are positively related. The main point of the study focuses on the implications of the relationship between health and income. In the early phases of income growth, the gains in health and the losses in environmental quality could cancel each other out and this challenges the idea that as incomes increase health would always improve. To empirically analyse these issues, the estimation of two-stage least squares model that focuses on the impact of income and the environment on health status, with environment being an endogenous variable is done. The results show that the environmental stress variable has a significant negative effect on health status. At the same time, gross national product (GNP) levels are shown to vary positively with health status. The Environmental Kuznet Curve is not found in this study, instead, it is found that the health gains obtained through improved incomes can be negated to a significant extent if the indirect effect of income acting via the environment is ignored. Research findings in this regard would be a useful policy instrument towards maximizing both the environmental and health gains that come with economic growth and development.